2022
DOI: 10.1093/ajcp/aqac088
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Fibrous Tumor of the Adrenal Gland

Abstract: Objectives Solitary fibrous tumor (SFT) is a mesenchymal neoplasm that can arise at various anatomic locations. It is characterized by inv12(q13q13)-derived NAB2::STAT6 fusion, resulting in the nuclear expression of STAT6. Primary SFT of the adrenal gland is rare. We launched a multi-institutional collaboration to comprehend the overarching demographics, clinical and follow-up, macroscopic, microscopic, IHC, and FISH features of 9 patients with SFT of the adrenal gland. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Notably, in cases documented by Yonly et al [ 6 ] and Kuribayashi et al [ 7 ], symptoms, particularly pain, were reported once the tumor reached approximately 10 cm in size. Another noteworthy consideration is the potential manifestation of paraneoplastic syndromes, such as refractory hypoglycemia due to the insulin-like growth factor release (known as Doege-Potter syndrome) [ 4 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, in cases documented by Yonly et al [ 6 ] and Kuribayashi et al [ 7 ], symptoms, particularly pain, were reported once the tumor reached approximately 10 cm in size. Another noteworthy consideration is the potential manifestation of paraneoplastic syndromes, such as refractory hypoglycemia due to the insulin-like growth factor release (known as Doege-Potter syndrome) [ 4 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that while STAT6 immunohistochemistry is a sensitive surrogate for detecting STAT6 fusion, it can also exhibit positivity in other entities, such as dedifferentiated liposarcoma, a more commonly occurring tumor in the retroperitoneum. Therefore, the inclusion of MDM2 amplification analysis is imperative in this context to differentiate from dedifferentiated liposarcoma [ 3 , 4 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solitary fibrous tumour (SFT) is an uncommon mesenchymal neoplasm of fibroblastic origin that usually involves the pleura and was first described by Klemperer and Rabin in 1931 [ 1 ]. Subsequently, it has been found that it can occur in numerous extrathoracic anatomical regions, such as the orbit [ 2 ], salivary glands [ 3 ], respiratory tract [ 4 ], mediastinum [ 5 ], adrenal glands [ 6 ], pelvis [ 7 ], skin [ 8 ], liver [ 9 ], and retroperitoneum [ 10 ]. However, SFTs occurring in the urinary bladder have seldom been reported.…”
Section: Introductionmentioning
confidence: 99%